Students' Perception of Using the Internet to Develop Reading Habits: A Case Study at the English Education Department of Universitas Kristen Indonesia - Bana, Arny (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
The internet ubiquity in education has flooded the teaching and learning process with digital tools and drastically changed many aspects of academic life, including students' reading habits. This study aimed at exploring students' perceptions of using the internet to develop reading habits. The study employed the qualitative descriptive method with survey design and involved 43 students of the English department of Universitas Kristen Indonesia Jakarta. Data was collected by means of a questionnaire consisting of 20 items. The results showed that 43% of the respondents had a positive perception that the internet developed their reading habits. However, the majority of them regarded reading as merely an activity for getting information to finish school assignments. They viewed the internet as the main source of information they needed to finish their learning assignments. Since about one-fifth of them preferred paper-based reading, it was concluded that not the whole of Generation Z members totally ignored printed reading materials.